1988
DOI: 10.1111/j.1348-0421.1988.tb01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron Microscopic Studies on Spore Coat Proteins of Bacillus megaterium

Abstract: An immunochemical staining technique for the spore coat proteins of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Collectively, these analyses indicate that the B. megaterium QM B1551 spore coat and exosporium are comprised and assembled from a substantially different subset of proteins to their orthologous Bacillus counterparts. Several biochemical‐led studies aimed at characterising the B. megaterium QM B1551 spore coat were published through the 1970s to early 1990s (Imagawa et al ., , ; Nishihara et al ., ; Takubo et al ., ). Unfortunately, these studies predated the availability of virtually any B. megaterium genomic information and tools for targeted genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these analyses indicate that the B. megaterium QM B1551 spore coat and exosporium are comprised and assembled from a substantially different subset of proteins to their orthologous Bacillus counterparts. Several biochemical‐led studies aimed at characterising the B. megaterium QM B1551 spore coat were published through the 1970s to early 1990s (Imagawa et al ., , ; Nishihara et al ., ; Takubo et al ., ). Unfortunately, these studies predated the availability of virtually any B. megaterium genomic information and tools for targeted genetic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that three proteins (P48, P36, and P22) absent in the mature spores of the OL deficient mutants are the components of OL, since they were found in SDS/DTT-soluble proteins of the higher density band. Recently, Imagawa et al (10) reported that P48 antigen was found only in the OL region from immunoelectron microscopic studies.…”
Section: Discussionmentioning
confidence: 99%